2013
DOI: 10.1007/978-3-642-37075-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Comodels and Effects in Mathematical Operational Semantics

Abstract: In the mid-nineties, Turi and Plotkin gave an elegant categorical treatment of denotational and operational semantics for process algebra-like languages, proving compositionality and adequacy by defining operational semantics as a distributive law of syntax over behaviour. However, its applications to stateful or effectful languages, incorporating (co)models of a countable Lawvere theory, have been elusive so far. We make some progress towards a coalgebraic treatment of such languages, proposing a congruence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We leave as future work to find out precisely how their Theorem 31 relates to our Theorem 4.3. In [1] effects with equations are added to the syntax generated by a free monad T , using as semantic domain a suitable final B-coalgebra in the Kleisli category of T (assumed to be enriched over ωcomplete pointed partial-orders). To prove adequacy of the semantics with respect to a given operational model, the authors use a result similar to our Theorem 4.3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We leave as future work to find out precisely how their Theorem 31 relates to our Theorem 4.3. In [1] effects with equations are added to the syntax generated by a free monad T , using as semantic domain a suitable final B-coalgebra in the Kleisli category of T (assumed to be enriched over ωcomplete pointed partial-orders). To prove adequacy of the semantics with respect to a given operational model, the authors use a result similar to our Theorem 4.3.…”
Section: Discussionmentioning
confidence: 99%
“…We check that λ preserves the distribution axiom: . We have thus shown that λ preserves E, and it follows, in particular, that R ω , +, ×, [0], [1] is a commutative semiring. This was shown directly in [31], but the proof uses bisimulation-up-to as well as the fundamental theorem of stream calculus, which cannot be added as an equation.…”
Section: Distributive Laws Over Plain Behaviour Functorsmentioning
confidence: 95%
See 1 more Smart Citation
“…We leave as future work to find out precisely how their Theorem 31 relates to our Theorem 4.3. In [1] effects with equations are added to the syntax generated by a free monad T , using as semantic domain a suitable final B-coalgebra in the Kleisli category of T (assumed to be enriched over ω-complete pointed partial-orders). To prove adequacy of the semantics with respect to a given operational model, the authors use a result similar to our Theorem 4.3.…”
Section: Discussionmentioning
confidence: 99%
“…We have thus shown that λ preserves E, and it follows, in particular, that R ω , +, ×, [0], [1] is a commutative semiring. This was shown directly in [31], but the proof uses bisimulation-up-to as well as the fundamental theorem of stream calculus, which cannot be added as an equation.…”
Section: Example 47 (Stream Calculus) Behavioural Differential Equamentioning
confidence: 95%